Brain region dependent molecular signatures and myelin repair following chronic demyelination - Samtani, Grace; Kim, Sunja; Michaud, Danielle; Hillhouse, Andrew E.; Szule, Joseph A.; Konganti, Kranti; Li, Jianrong (Frontiers in Cellular Neuroscience, 2023)
Multiple sclerosis (MS) is the most prevalent demyelinating disease of the central nervous system, characterized by myelin destruction, axonal degeneration, and progressive loss of neurological functions. Remyelination is considered an axonal protection strategy and may enable functional recovery, but the mechanisms of myelin repair, especially after chronic demyelination, remain poorly understood. Here, we used the cuprizone demyelination mouse model to investigate spatiotemporal characteristics of acute and chronic de- and remyelination and motor functional recovery following chronic demyelination. Extensive remyelination occurred after both the acute and chronic insults, but with less robust glial responses and slower myelin recovery in the chronic phase. Axonal damage was found at the ultrastructural level in the chronically demyelinated corpus callosum and in remyelinated axons in the somatosensory cortex. Unexpectedly, we observed the development of functional motor deficits after chronic remyelination. RNA sequencing of isolated brain regions revealed significantly altered transcripts across the corpus callosum, cortex and hippocampus. Pathway analysis identified selective upregulation of extracellular matrix/collagen pathways and synaptic signaling in the chronically de/remyelinating white matter. Our study demonstrates regional differences of intrinsic reparative mechanisms after a chronic demyelinating insult and suggests a potential link between long-term motor function alterations and continued axonal damage during chronic remyelination. Moreover, the transcriptome dataset of three brain regions and over an extended de/remyelination period provides a valuable platform for a better understanding of the mechanisms of myelin repair as well as the identification of potential targets for effective remyelination and neuroprotection for progressive MS.